THE SPECIFICS OF FORM OF CLINICAL REASONING ON PRACTICAL CLASSES AT GENERAL SURGERY - Дмитрів, І. В.; Волошин, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article addresses the specifics of teaching practical classes in the fundamentals of clinical reasoning at general surgery departments within the framework of the “MUMEENA” project. The author suggests a methodology of teaching such a class by discussing a clinical case of pain in the ankle and foot. The goal of the class is to teach how to diagnose a disease by taking into account patient complaints, anamnesis and objective examination data, how to develop examination and treatment schemes, to evaluate their effectiveness and to propose recommendations as to the patient’s lifestyle and work patterns. The proposed methodology of teaching practical classes in clinical reasoning is aimed at engaging all the students in the learning process, encouraging them to gain profound knowledge of a certain pathology as well as developing analytical skills and motivating self-improvement.